2023
DOI: 10.1186/s12866-023-02906-w
|View full text |Cite
|
Sign up to set email alerts
|

Detection of blaNDM−1,mcr-1 and MexB in multidrug resistant Pseudomonas aeruginosa isolated from clinical specimens in a tertiary care hospital of Nepal

Abstract: Introduction Pseudomonas aeruginosa is an opportunistic pathogen, which causes healthcare-associated infections in immunosuppressed patients. They exhibit resistance to multiple classes of antibiotics via various mechanisms such as the over-expression of efflux pumps, decreased production of the outer membrane protein (D2 porin), over-expression of the chromosomally encoded AmpC cephalosporinase, modification of drugs, and mutation(s) at the target site of the drug. The bacteria also develop an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
0
0
Order By: Relevance
“…Previous reports from Pakistan detected bla NDM-1 , bla IMP , bla VIM , bla OXA-48 carbapenemases in CRPA [21,71,72,85,93,94]. These findings are supported by various global reports [14,73,90,[95][96][97][98][99][100][101]. On the other hand, the detection of bla KPC among CRPA was reported infrequently in Pakistan [94]; however, an increasing trend in the global dissemination of bla KPC -harboring P. aeruginosa has been observed [22,28,[102][103][104][105][106][107][108].…”
Section: Discussionsupporting
confidence: 54%
“…Previous reports from Pakistan detected bla NDM-1 , bla IMP , bla VIM , bla OXA-48 carbapenemases in CRPA [21,71,72,85,93,94]. These findings are supported by various global reports [14,73,90,[95][96][97][98][99][100][101]. On the other hand, the detection of bla KPC among CRPA was reported infrequently in Pakistan [94]; however, an increasing trend in the global dissemination of bla KPC -harboring P. aeruginosa has been observed [22,28,[102][103][104][105][106][107][108].…”
Section: Discussionsupporting
confidence: 54%
“…Current studies have shown that mexAB-oprM and mexXY-oprA efflux operons play an important role in antibiotic resistance in Pseudomonas aeruginosa isolates from Tabriz, Iran [33]. Pseudomonas aeruginosa was isolated from clinical specimens from a tertiary care hospital in Nepal, and MexB was detected in the multi-drug-resistant Pseudomonas aeruginosa [34]. Recent studies have shown that Pseudomonas aeruginosa isolates were multidrug-resistant with a high level of efflux pump expression of the MexA gene [35].…”
Section: Discussionmentioning
confidence: 99%